Maturity assessment of social customer knowledge management (SCKM) using fuzzy expert system - Lak, Behzad; Rezaeenour, Jalal (Journal of Business Economics and Management, 2018)
Organizations which provide electronic services do not have a logically structured strategy for implementing Customer Knowledge Management through Social media (SCKM). By assessing the position of SCKM, organizations can have a clear understanding of their maturity level and find their future investment interests. This research examined the maturity assessment of SCKM utilizing a fuzzy expert system. It consisted of a-four-stage procedure. The maturity model is based on 11 critical success factors, including strategy, leadership, information technology, knowledge management, culture, process, resources, business intelligence, security, social customer, and assessment. Results showed that the studied organization has covered 48.2% of maturity on the first level and 51.8% on the second level. Thus, to increase productivity, it is indispensable for organizations to act in a targeted way. The fuzzy expert system is not designed specifically for a case study, but can be utilized as a reference for in-depth analysis of the organizational readiness for SCKM implementation and development within organizations, which provide e-services applications.